ANALISA PENGARUH CURRENT RATIO (CR), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM DI PERUSAHAAN SEKTOR TEKNOLOGI YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2015-2023 - Dandono, Yustinus Rawi; Azzahra, Cahaya Sarah (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to analyze the effect of Current Ratio (CR), Return on Equity (ROE), Earnings Per Share (EPS), and Debt to Equity Ratio (DER) on stock prices. The sample size for this study was four technology companies listed on the Indonesia Stock Exchange between 2015 and 2023, using a purposive sampling method. The method used in this study was multiple linear regression, involving classical assumption tests, followed by partial significance testing using the t-test, and to determine the effect simultaneously, the f-test was used with a significance level of 5%. The results showed that partially, CR and ROE had a significant negative effect, EPS had a significant positive effect, and DER had no significant effect on stock prices. Simultaneously, CR, ROE, EPS, and DER had an effect on stock prices. The adjusted R-squared value in this study was 0.388, indicating that the independent variables explained 38.8% of the dependent variable, while the remaining 61.2% was explained by other independentvariables outside the model.